Are self-reported unhealthy food choices associated with an increased risk of breast cancer? Prospective cohort study using the British Food Standards Agency nutrient profiling system. Issue 6 (8th June 2017) - Deschasaux, Mélanie; Julia, Chantal; Kesse-Guyot, Emmanuelle; Lécuyer, Lucie; Adriouch, Solia; Méjean, Caroline; Ducrot, Pauline; Péneau, Sandrine; Latino-Martel, Paule; Fezeu, Léopold K; Fassier, Philippine; Hercberg, Serge; et al.
Abstract : Objectives: French authorities are considering the implementation of a simplified nutrition labelling system on food products to help consumers make healthier food choices. One of the most documented candidates (Five-Colour Nutrition Label/Nutri-score) is based on the British Food Standards Agency Nutrient Profiling System (FSA-NPS), a score calculated for each food/beverage using the 100 g amount of energy, sugar, saturated fatty acid, sodium, fibres, proteins, and fruits and vegetables. To assess its potential public health relevance, studies were conducted on the association between the nutritional quality of the diet, measured at the individual level by an energy-weighted mean of all FSA-NPS scores of foods usually consumed (FSA-NPS dietary index (FSA-NPS DI)), and the risk of chronic diseases. The present study aimed at investigating the relationship between the FSA-NPS DI and breast cancer risk. Design: Prospective study. Setting: Population based, NutriNet-Santé cohort, France. Participants: 46 864 women aged ≥35 years who completed ≥3 24-hour dietary records during their first 2 year of follow-up. Primary outcome measure: Associations between FSA-NPS DI and breast cancer risk (555 incident breast cancers diagnosed between 2009 and 2015) were characterised by multivariable-adjusted Cox proportional hazard models. Results: A higher FSA-NPS DI (lower nutritional quality of the diet) was associated with an increased breast cancer risk (HR1-point increment =1.06 (1.02–1.11), p=0.005; HRQ5vs.Q1 =1.52 (1.11–2.08), p trend=0.002). Similar trends were observed in premenopausal and postmenopausal women (HR1-point increment =1.09 (1.01–1.18) and 1.05 (1.00–1.11), respectively). This study was based on an observational cohort using self-reported dietary data, thus residual confounding cannot be entirely ruled out. Finally, this holistic approach does not allow investigating which factors in the diet most specifically influence breast cancer risk. Conclusions: These results suggested that unhealthy food choices, as characterised by the FSA-NPS, may be associated with an increase in breast cancer risk, supporting the potential public health relevance of using this profiling system in the framework of public health nutritional measures.